Zr and V-doped effect on Martensitic transformations and magnetic properties of NiMnIn shape memory alloy - Tasgin, Yahya; Kanca, M. Sait; Kok, Mediha; Oner, Ecem Ozen; Guler, Omer (Elsevier, 2024)
In this study, the elements vanadium (V) and zirconium (Zr) were doped separately as a fourth element to the ternary NiMnIn Heusler magnetic shape memory alloy and the alloys were produced as ingots by arc -melting method. The shape memory properties, microstructures, magnetic and microstructural changes of these new alloys were investigated in detail. The vanadium (V) and zirconium (Zr) elements doped into the alloy caused a decrease in the transformation temperature values of the alloy, but did not cause a significant change in its magnetic properties. The master sample, which has low hysteresis, undergoes a phase transition from the martensite phase to the austenite phase due to an increase in the nucleation of austenite phases at the twinning boundaries. Here, the vanadium and zirconium doping of the alloy caused an increase in the strength and ductility values of the alloy and this caused the formation of the second phase. Due to the increase of this phase formation in the alloy, it can be said that there is a slight decrease in the shape retention of the alloy.
Keywords: Shape memory effect; Vanadium (V) and zirconium (Zr) doping; Phase transformation; Thermal characterization and magnetization